Complete genome sequence of endophytic nitrogen-fixing Klebsiella variicola strain DX120E - Lin, Li (Stand Genomic Sci, 2015)
Klebsiella variicola strain DX120E (=CGMCC 1.14935) is an endophytic nitrogen-fixing bacterium isolated from sugarcane crops grown in Guangxi, China and promotes sugarcane growth. Here we summarize the features of the strain DX120E and describe its complete genome sequence. The genome contains one circular chromosome and two plasmids, and contains 5,718,434 nucleotides with 57.1% GC content, 5,172 protein-coding genes, 25 rRNA genes, 87 tRNA genes, 7 ncRNA genes, 25 pseudo genes, and 2 CRISPR repeats.